Stochastic growth and regime shift risk in renewable resource management - Nkuiya, Bruno; Diekert, Florian (Ecological economics)
Renewable resources are affected by both environmental variability, which makes the year-to-year stock growth uncertain, and the risk of irreversible events (e.g., a stock collapse). Little is known about how a renewable resource harvester would optimally respond to the combined effects of both sources of risk. In this paper, we propose a simple dynamic resource model to investigate this issue. For some structures of the harvesting cost function, we find that anticipating a higher variability in biological growth induces a cautious management policy, but only when regime shift risk is accounted for. Accounting for the risk of regime shift may prescribe large changes in management responses to anticipated random changes in biological growth whereas ignoring such a risk prescribes small changes in management. Optimal escapement is not constant but varies across all periods when the planning horizon is finite and the regime shift risk is endogenous.